A conditional probability of default under the influence of both systematic and idiosyncratic components - Sarmiento, Camilo (Seventh Sense Research Group (SSRG), 2020)
In this article, we relax the assumption of a fully granular portfolio underpinning the Basel II risk weights for credit risk in determining capital requirements. To do so, we model losses under an adverse scenario that stems from both the systematic and idiosyncratic components. The generalization requires the use of a numerically derived distribution function via simulation. Unlike previous work, our method is sufficiently flexible to accommodate a fattailed distribution in the idiosyncratic component. The idiosyncratic component is pertinent for a non-granular portfolio.

En este artículo, flexibilizamos el supuesto de una cartera completamente granular que sustenta las ponderaciones de riesgo de crédito de Basilea II al determinar los requisitos de capital. Para ello, modelamos las pérdidas bajo un escenario adverso que surge tanto del componente sistemático como del idiosincrásico. La generalización requiere el uso de una función de distribución derivada numéricamente mediante simulación. A diferencia del trabajo anterior, nuestro método es lo suficientemente flexible como para acomodar una distribución de cola ancha en el componente idiosincrásico. El componente idiosincrásico es pertinente para una cartera no granular.
Keywords: Distribución (Teoría de la probabilidad); Distribution (Probability theory); Riesgo (Economía); Risk; Crédito; Credit; Probability of Default; Adverse Scenario; Systematic; Idiosyncratic; Probabilidad de incumplimiento; Escenario adverso; Sistemático; Idiosincrásico